If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 21 = 2x + 13 Reorder the terms: 21 + 3x = 2x + 13 Reorder the terms: 21 + 3x = 13 + 2x Solving 21 + 3x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 21 + 3x + -2x = 13 + 2x + -2x Combine like terms: 3x + -2x = 1x 21 + 1x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 21 + 1x = 13 + 0 21 + 1x = 13 Add '-21' to each side of the equation. 21 + -21 + 1x = 13 + -21 Combine like terms: 21 + -21 = 0 0 + 1x = 13 + -21 1x = 13 + -21 Combine like terms: 13 + -21 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| f(x+5)=6x-8 | | 2(n+.3333333333333)=1.666666666666n+1+.5n-.33333333333 | | 4(x-2)=2(x-4)+2 | | 3-7y+4=2y+11-7y | | 120(20)=50(x) | | (2(3)-a)(3+b)(3+c)=0 | | x-(3-x+1)=-x-4 | | x-3(-x+1)=-x-4 | | f(x)=1+ln(1+ln(1+ln(1+x))) | | 19-(5m+7)=4+2m-13 | | 60(36)=60(k) | | (2b-1)i+(a+3)=4-8i | | 4t^2-20t-25=0 | | (3x-5)+(12x)=90 | | (3-2i)-(2x+yi)=7+6i | | 3a-10+4a=5a-7 | | 3.7b+7=8.1b-18.4 | | 42(z)=35(28) | | 4+3+-7=4+-7 | | 36(x)=45(32) | | (2x)=(2y-x) | | (3x-5)=(12x) | | C(x)=.6x+30 | | x-3(-x)+1=-x-6 | | 18(5)=7.5(x) | | 10-(3x-5)=11-4x | | 8+3x=132 | | 10x-50=7x-20 | | x-(3-x+1)=-x-6 | | X^2-11x+48=0 | | 11x-8=x | | 0=(-.02x^2)+1.7x+5.1 |